PERBANDINGAN CYSTATIN C DENGAN PARAMETER UJI FUNGSI GINJAL LAINNYA - Pusparini . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
The Gold standard for the evaluation of the glomerular filtration rate (GFR) is inulin clearance, but in widespread use is prevented by several technical difficulties. The most commonly used marker for GFR is serum creatinine alone or in conjunction with 24 hoururine collection for determination of creatinine clearance, but these marker have several limitation include following: influence of age,sex, muscle mass on endogenous creatinine production, dietary intake and the difficulties of 24 hour urine collection. Fifty six patientwith chronic renal failure and 53 control had analyze for serum creatinin, creatinine clearance and serum cystatin C. The chronic renalfailure patient aged range from (64 + 14.54) year and the control group aged range from (62.5+ 17.5) year. The proposed of this studywas to compare cystatin C with another parameter for renal function test. The result showed that in control group serum creatinineand creatinine clearance had influence with age, sex and body mass index, but serum cystatin C was not. The normal value of cystatinC was (0.85 + 0.13) mg/dL In chronic renal failure group there were significant correlation between level of cystatin C with creatininclearance (p = 0.000, r = 0.69). The level of cystatin C increase higher than serum creatinine in patient with low clearance creatinine.In control group we were determined low creatinine clearance in patient with normal serum creatinine and cystatin C.